Band gap and experimental study in phononic crystals with super-cell structure - Yingjian Sun; Yingjie Yu; Yayu Zuo; Lili Qiu; Mingming Dong; Jiatong Ye; Jun Yang (Results in Physics, 2019)
The phononic crystals (PCs) have the wide application prospects in the field of regulating sound waves and vibration reduction due to their unique band gaps (BGs) characteristics. In this paper, a new phononic crystal of which the super-cell is composed of a simple combination of traditional PCs is proposed to open BGs in low frequency range. The dispersion relations, displacement fields of eigenmodes and transmission spectra are obtained by the finite element method. Both theoretical and experimental results verify that the improved PCs obtained low-frequency BGs range from 153 Hz to 196 Hz, which is generated by the rigid body resonance. The effect of the geometrical parameters and shapes on the dispersion relations are further analysed and discussed. Finally, the experimental transmission spectrum of the improved PCs is presented by a hammer test. This study might provide theoretical and practical support to the design of PCs components in the field of low-frequency vibration reduction. Keywords: Phononic crystals, Super-cell, Vibration reduction